Investigating Inconsistencies between Mikalojus Daukša’s Catechism (1595) and Its Polish Original - Pajėdienė, Jūratė (Vertimo studijos, 2018)
[full article and abstract in Lithuanian; abstract in English] The article discusses the inconsistencies between the first Lithuanian Catholic book, Mikalojus Daukša’s Catechism (DK, 1595), and its Polish original, and the reasons that caused these inconsistencies. From the perspective of the text’s origin, DK consists of two works of a different type and different authorship: KATHECHISMAS and Trumpas Budas Paſiſákimo. When comparing the Lithuanian texts of the books comprising this so called ‘convolute’ and the Polish original, it is not difficult to notice that DK (in particular its first part, Kathechismas) contains a number of insertions that do not appear in the Polish original. The analytic comparison between the texts and their originals enables us to describe Daukša as an author who was highly concerned with the logic, order and sound of the discourse. The entirety of the inconsistencies shows the translator’s efforts to render as understandable and coherent a text to the reader as possible and reveals the translator’s careful attention to the wording of theological propositions. The situation of coincidences and inconsistencies between the Decalogue presented in Kathechismas and the model of the Polish original is especially interesting. After the wording of the Decalogue presented in DK, which differs from the Polish original in lexical details or entire phrases, is compared with the Decalogue presented in the catechisms by Mažvydas (1547) and Vilentas (1579), an auxiliary role of those sources reveals in Daukša’s choice of the Decalogue’s sentence structure, certain phrases or individual lexical units.